The influence of student teachers' personal learning strategies and teacher experiences on their implicit beliefs on teaching and learning - Encabo, Henry C. (Animo Repository, 2001)
This project paper is designed to describe how school-related experiences like personal learning strategies and teacher experiences influence student teachers beliefs.The proposed study is basically qualitative in nature. The study is descriptive of student teachers implicit beliefs and experiences. Moreover, it takes on a case study approach in data gathering and interpretation.Five student teachers that are practicing to teach secondary mathematics will be tapped as respondents to the proposed study. Selection would be on the basis of their having finished all their major and education subjects and they should not be taking any math subject, as a back subject at the time of the study. Moreover, they should come from the group of graduating students of Brokenshire College that had undergone the whole course in said institution. Among the qualified student teachers, five would be randomly selected and invited to join the study.The researcher, having been trained in both theory and practice of qualitative research will serve as interviewer, participant observer or an archive analyst. He will be assisted by trained and locally based psychologists.Data analysis will be done in three phases: the identification of teachers implicit beliefs and experiences, the clustering of such, and connections between the two. Identification of student teachers implicit beliefs will be guided by the definitions of Pajares (1992), Nespor (1987) and Schraw, Bruning and Ronning (2000) and other authors of similar studies. The data will be assessed for emerging themes (Flores, undated) and will serve as basis for identifying beliefs. Literature will be consulted for such themes and beliefs. Identifying student teacher experiences will also proceed in a similar manner to the identification of student teachers implicit beliefs. Clustering of beliefs will be done through constant comparative analysis of logically related concepts. Connections between experiences and beliefs will be established by examining parallelisms and qualitative relationships between the two.